Islamic civilization and its challenges with current issues - Mahmod hamdi Zaqzoq, (Institut Islam Hadhari Universiti Kebangsaan Malaysia, 2009)
Civilisation from Islamic perspective is the implementations of God’s will in developing physical and spiritual worlds. The action is considered as a human success to justify himself as vicegerent of God. By this main, a man can have continuous relation with his Creator. This relation will put man in a right tract in his living part, and will not make him astray. This paper explores challenges facing Muslim society in order to re-establish the glory of Islamic civilisation in future. The paper also emphasizes that by having strong Islamic civilisation, the ummah can face the challenge including the current challenge of globalisation